2016
DOI: 10.1016/j.jsbmb.2015.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of AKR1C3 exposes a potential epigenetic susceptibility in prostate cancer cells

Abstract: Background The aldo-keto reductase 1C3 (AKR1C3) has been heavily implicated in the propagation of prostate malignancy. AKR1C3 protein is elevated within prostate cancer tissue, it contributes to the formation of androgens and downstream stimulation of the androgen receptor (AR). Elevated expression of AKR1C3 is also reported in acute myeloid leukemia but the target nuclear receptors have been identified as members of the peroxisome-proliferator activated receptor (PPARs) subfamily. Thus, AKR1C3 cancer biology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Knockdown of AKR1C3 was accompanied by a significantly reduced expression of a range of histone deacetylases, transcriptional co-regulators, and increased sensitivity towards SAHA, a clinically approved histone deacetylase inhibitor. [85] Looking beyond PCa, UGT2B17 has been identified as a disease accelerator in chronic lymphocytic leukemia [86], and knockdown of UGT2B17 in an endometrial carcinoma cell line resulted in an increase in apoptosis in association with downregulation of the anti-apoptotic protein Mcl-1, and upregulation of the pro-apoptotic target of Mcl-1, Puma [87]. While the mechanism of UGT2B17 involvement in these tumors remains to be elucidated, these reports underscore the potential role of these enzymes in non-steroid metabolizing capacities.…”
Section: A Non-classical Role For Dht Metabolizing Enzymesmentioning
confidence: 99%
“…Knockdown of AKR1C3 was accompanied by a significantly reduced expression of a range of histone deacetylases, transcriptional co-regulators, and increased sensitivity towards SAHA, a clinically approved histone deacetylase inhibitor. [85] Looking beyond PCa, UGT2B17 has been identified as a disease accelerator in chronic lymphocytic leukemia [86], and knockdown of UGT2B17 in an endometrial carcinoma cell line resulted in an increase in apoptosis in association with downregulation of the anti-apoptotic protein Mcl-1, and upregulation of the pro-apoptotic target of Mcl-1, Puma [87]. While the mechanism of UGT2B17 involvement in these tumors remains to be elucidated, these reports underscore the potential role of these enzymes in non-steroid metabolizing capacities.…”
Section: A Non-classical Role For Dht Metabolizing Enzymesmentioning
confidence: 99%
“…As reported, AKR1C3 is a multifunctional enzyme that catalyzes multiple hormones and xenobiotic metabolism (Dufort et al, 1996; Matsuura et al, 1998). A growing number of studies have shown that overexpressed AKR1C3 occurs in multiple types of human cancer and is involved in the development of human cancer and chemotherapy resistance, such as hepatocellular carcinoma, prostate cancer, breast cancer and esophageal cancer (Doig et al, 2016; Li, 2018a; Pan et al, 2022; Xu et al, 2017). More intriguingly, AKR1C3 exhibits elevated expression in thyroid cancer tissues, and high AKR1C3 expression tends to have a poor prognosis (Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, as previous studies stated, AKR1C1 could mediate the invasive potential and drug resistance of metastatic bladder cancer cells, and AKR1C1 was highly expressed in metastatic lesions of human bladder cancer patients 29 . AKR1C3, comes from the same family as AKR1C1, has not been proved to have similar functions as AKR1C1 in bladder cancer, but it is often overexpressed in prostate cancer tissues and prostate cancer cell lines 30 . AKR1C3 catalyzes the formation of prostaglandin (PG) F2α and 11β-PGF2α from PGH2 and PGD2, respectively 31 .…”
Section: Discussionmentioning
confidence: 99%